Bacterial biofilms on the sinus mucosa of human subjects with chronic rhinosinusitis - Sanderson, Alicia R; Leid, Jeff G; Hunsaker, Darrell (The Laryngoscope, 2006)
Chronic rhinosinusitis (CRS) is a common disease poorly controlled by antibiotics. Postulated etiologies of CRS include allergy, fungi, functional factors, and biofilm. We presented a preliminary study demonstrating bacterial biofilms' presence on the sinus mucosa of patients with CRS using fluorescent in situ hybridization (FISH). The advantage of FISH in biofilm identification is that it is the only method that identifies the specific bacteria creating the biofilm matrix. We now present the results of a larger series of patients. Patients with CRS scheduled for sinus surgery were enrolled in the study. Biopsies of the sinus mucosa and cultures were taken at the time of surgery. Control samples were taken from patients undergoing septoplasty. Specimens underwent FISH testing for Streptococcus pneumoniae, Staphylococcus aureus, Haemophilus influenza, and Pseudomonas aeruginosa. Bacterial biofilms were present on 14 of 18 specimens. The predominant species were H. influenzae, S. pneumoniae, and S. aureus. P. aeruginosa biofilm was not identified on any specimens. The intraoperative cultures of the planktonic bacteria present in the sinuses did not correlate with the biofilms identified. Two of the five control samples were positive for biofilm. The presence of biofilms on the mucosa of patients with CRS offers a possible cause of antimicrobial therapy failure and could change the approach to treatment. However, the presence of biofilms on healthy control samples implies that biofilms may simply be colonizers. The precise role that biofilms play in CRS still remains to be determined. Further studies with larger sample sizes are needed.